Ophiostomatoid Fungi Associated with the Ambrosia Beetle Platypus cylindrus in Cork Oak Forests in Tunisia - Amani Bellahirech; Maria Lurdes Inácio; Mohamed Lahbib Ben Jamâa; Filomena Nóbrega (Tunisian Journal of Plant Protection, 2018)

(untitled)
Cork oak (Quercus suber) is a unique species of the Western Mediterranean region and over the last decades it has been threatened by several pests and diseases. Amongst the main dangerous pests, the ambrosia beetle Platypus cylindrus (the oak pinhole borer) has a key role on the process of cork oak decline namely in Portugal, Morocco, and Algeria. However, in Tunisia, where cork oak forests cover around 90.000 ha of the territory, this insect continues to have a secondary pest status. As all ambrosia insects, P. cylindrus is able to establish symbiotic relationships with fungi and it is known as the vector of ophiostomatoid fungi, a group including primary tree pathogens. The aim of this study was to identify these beetle-associated fungi in Tunisian forests and to understand the contribution of this association in cork oak decline by comparing with the results from other countries. The present study was conducted in 2012 in ten cork oak forests in the western-north of Tunisia and focused on ophiostomatoid fungi associated with the cork oak pinhole borer. Twenty four isolates were grouped based on morphological identification, and five representative isolates were included in phylogenetic analyses based on sequence data of ITS and β-tubulin loci. The fungi were assigned to five species namely Raffaelea montetyi, R. canadensis, Ophiostoma sp., O. tsotsi and O. quercus, some of them were already reported in Portugal and Algeria to be associated with cork oak decline. All these species were identified and reported for the first time in Tunisia to be associated with P. cylindrus in cork oak trees and their role in the cork oak loss of vitality needs to be investigated.